The Role of Care in Enviromental Aesthetics - Saito, Yuriko (The Nordic Journal of Aesthetics, 2025)
We manage everyday life with the help of artifacts, a major part of our environment. Although we are the ones who create and operate artifacts, their service for us can be characterized as their care for us, indicated by our frequent attribution of morally-charged aesthetic qualities to them. Their care for us suggests our reciprocal responsibility for caring for them not only by careful handling to avoid their breakage and destruction but also by a more proactive work of care and maintenance, such as cleaning. Considered ‘reproductive labor,’ care and maintenance work does not garner the recognition or appreciation accorded to ‘productive labor’ which requires creativity and imagination. However, care and maintenance work has surprisingly rich aesthetic potentials, as well as an existential significance for encouraging our engagement with the world. We lose something important if we are completely liberated from such work, the direction promoted by technological advancement.